When numbers don’t satisfy science: multicenter studies and digital protocols - Rivera, Fabrizio; Comba, Luca; Perticarini, Loris; Benazzo, Francesco (Lo Scalpello - Journal, 2021)
Megaprostheses were introduced in oncological orthopedic surgery for reconstruction after bone tumor resections with good results; more recently, megaprostheses have been receiving an increasing role even in non-neoplastic hip and knee conditions like periprosthetic and very comminuted osteoporotic fractures and in treatment for resistant non-union of femur fractures. Nevertheless, literature about the use of megaprosthesis, especially in non-oncological musculoskeletal conditions, is still lacking high evidence level studies showing long-term outcomes. The purpose of this paper is carry out a review of the current megaprosthesis literature and present a multicenter study on a new prosthetic implant (“SMS multicentric study”), collecting the data on the use of a single implant (Smart Modularity System/SMS) in 11 orthopedic centers in order to obtain clinical and radiographic results.